The Regional Supervisory Assembly’s Role in the Submission Delaying of the Notary Protocol by Heirs to Notary Recipient Protocol - Indarta, Didiek Wahju; Damayanti, Miranda (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This study aims to analyze the role of the Regional Supervisory Council (MPD) in overseeing the submission of the notary protocol by the heirs to the protocol recipient notary, as well as the impact of the delay in submission. The research method applied in the preparation of this research is normative legal research. Normative legal research is a method that focuses on the study of positive law, namely the law that applies at a certain time and place. Notarial protocols are important documents that function as state archives and legal evidence. In this context, MPD has the responsibility to ensure that heirs fulfill their legal obligations in submitting notarial protocols on time. This research identifies various factors that cause delays in submission, including heirs' lack of awareness and knowledge, complicated administrative processes, as well as indifference to legal obligations. In addition, the research also revealed the negative impact of the absence of effective sanctions against late submission of protocols, which can result in legal uncertainty, losses for related parties, and a decrease in the integrity of the legal system. The results show that to improve the effectiveness of MPD supervision, socialization efforts, strengthening regulations, and enforcement of clear sanctions are needed. Thus, this study provides recommendations to improve the notary protocol submission mechanism and increase heirs' compliance with their legal obligations.